Art Plaza in Makassar: Determining Location and Site in Building Planning - Imam Firmansyah (Newinera Publisher, 2020)
The planning of the Art Plaza in Makassar can fulfill the need to encourage the spirit of work and creativity for artists and build a forum and as a bridge of appreciation of art and culture with the community. Location determination analysis is based on taking into account the basic considerations taken and the division of Makassar City and several factors that need to be considered in determining the location of Plaza Seni, including; accessibility for transportation and communication lines, location must be easily accessible to the community or close to the highway and available infrastructure and facilities easily, for example; available pedestrian, accessible for people with disabilities. An adequate location for planning an art plaza is in the district of Ppanakukkang, Kelurahan Paropo. From the location of the site, it can be concluded that the chosen site is feasible enough to become a planning site for the construction of Plaza Seni in Makassar.